COMPARISON OF BACTERIAL ORGANISMS INSIDE THE UTERUS FOLLOWING TIMELY AND UNTIMELY INSEMINATIONS AND TWO TECHNIQUES OF AI GUN INSERTION IN CATTLE - KUTTY C, IBRAHEEM; C P, ABDUL AZEEZ; RAVISHANKAR, CHINTU (The Indian Journal of Animal Reproduction, 2021)
Various factors predisposing high incidence of infertility caused by non-specific uterine infections among AI (artificial insemination) bred cattle include inadequacy of aseptic practices, faulty techniques and untimely insemination. The present study was taken up to compare bacterial organisms present inside the uterus following two techniques of AI gun insertion (M1 and M2) during and after estrus period. Out of the 32 samples 43.75% showed bacterial growth and among the 8 samples from cows, 62.5% had microbial growth as against 37.50 % from heifers (n=24). Gun insertion contacting the vaginal fornix resulted more samples of bacterial growth (62.50%) as against direct insertion (25.00%). Comparing methods of insertion together with stages of cycle, chances of bacterial contamination was significantly higher (P 0.01%) during post estrual phase insertion with more contact on vaginal fornix (21.88%) as against direct cervical insertion during proper estrus (3.13%). It is concluded that untimely AI forms the major reason for increased occurrence of endometritis leading to infertility among AI bred cattle.